Cost of Treating Pediatric Cancer at the Butaro Cancer Center of Excellence in Rwanda - Neal, Claire (J Glob Oncol, 2018)
PURPOSE: Improvements in childhood survival rates have been achieved in low- and middle- income countries that have made a commitment to improve access to cancer care. Accurate data on the costs of delivering cancer treatment in these settings will allow ministries of health and donors to accurately assess and plan for expansions of access to care. This study assessed the financial cost of treating two common pediatric cancers, nephroblastoma and Hodgkin lymphoma, at the Butaro Cancer Center of Excellence in rural Rwanda. METHODS: A microcosting approach was used to calculate the per-patient cost for Hodgkin lymphoma and nephroblastoma diagnosis and treatment. Costs were analyzed retrospectively from the provider perspective for the 2014 fiscal year. The cost per patient was determined using an idealized patient receiving a full course of treatment, follow-up, and recommended social support in accordance with the national treatment protocol for each cancer. RESULTS: The cost for a full course of treatment, follow-up, and social support was determined to be between $1,490 and $2,093 for a patient with nephroblastoma and between $1,140 and $1,793 for a pediatric patient with Hodgkin lymphoma. CONCLUSION: Task shifting, reduced labor costs, and locally adapted protocols contributed to significantly lower costs than those seen in middle- or high-income countries.